Diabetic Ketoacidosis in Pregnancy: A Case Report - Febrian Daru Setiawan; Hermina Novida (Indian Journal of Forensic Medicine & Toxicology, 2022)
A 31-year-old pregnant woman complained of vomiting, shortness of breath, fever, general weakness,painful and frequent urination with sign of hypertension, tachycardia, Kussmaul breathing. Laboratorystudies showed neutrophilia, leukocytosis, hyperglycemia, hypokalemia, ketonuria, metabolic acidosis,low C-peptide, low Thyroid Stimulating Hormone, high FT4 and Staphylococcus in blood culturewas diagnosed with Diabetic Ketoacidosis, pregestational Type 1 Diabetes Mellitus, hyperemesisgravidarum, 14 weeks of pregnancy, suspect Urinary Tract Infection, hypokalemia, hypertension, andsubclinical hyperthyroidism. Besides, the patient blamed the fetus on causing the disease and financialproblem so that the patient also was diagnosed with episode of moderate depression. The patient receivedKVT1 diet therapy, fluid replacement therapy, insulin therapy, correction of hypokalemia, correctionof acidosis metabolic antibiotic and anti-hypertension. The therapies aimed to prevent maternal andfetal morbidity. Supportive psychotherapy therapy, relaxation therapy, and family psychoeducationwere also needed to improve patient’s compliant. The patient was also suggested to consult for familyplanning and glucose control before conception.